1999
DOI: 10.1104/pp.120.4.1043
|View full text |Cite
|
Sign up to set email alerts
|

The Endogenous Sulfated Pentapeptide Phytosulfokine-α Stimulates Tracheary Element Differentiation of Isolated Mesophyll Cells of Zinnia1

Abstract: Dispersed zinnia (Zinnia elegans) mesophyll cells cannot differentiate into tracheary elements (TEs) at low cell density conditions even if auxin and cytokinin are present in the medium, indicating the involvement of intercellular interactions during the initiation and/or subsequent progresses in TE differentiation. When zinnia cells were incubated at a low density (2.5 ؋ 10 4 cells mL ؊1 ) in TE-inductive medium in the presence of various concentrations of phytosulfokine (PSK)-␣, which was originally identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(69 citation statements)
references
References 14 publications
0
66
0
3
Order By: Relevance
“…TE formation has also been found to coincide with changes in the extracellular pH of the culturing medium (24). Effort has been focused on the intercellular communication during this process, with several xylogen compounds having been described (25,26). The implication of PCD provides another paradigm for induction and regulation of the tracheid cell death.…”
mentioning
confidence: 99%
“…TE formation has also been found to coincide with changes in the extracellular pH of the culturing medium (24). Effort has been focused on the intercellular communication during this process, with several xylogen compounds having been described (25,26). The implication of PCD provides another paradigm for induction and regulation of the tracheid cell death.…”
mentioning
confidence: 99%
“…Subsequent studies demonstrated the existence of PSK-K in CM derived from both monocot [7] and dicot [8,9] cell cultures. Furthermore, isolation of a rice (Oryza sativa L.) cDNA, OsPSK, encoding a putative PSK-K precursor has been achieved [10] and it was also shown that rice suspension cells contain both speci¢c high-and low-a¤n-ity saturable PSK-K binding sites on their plasma membranes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Tracheary element differentiation occurs synchronously at high frequency above initial cell densities of 4.2 × 10 4 cells mL L −1 , but is significantly suppressed below this threshold. This result indicates that intercellular interactions are involved in the initiation and/or subsequent progresses in TE differentiation (Matsubayashi et al 1999). McCann et al (2000) reported that plant condition and leaf age are critical factors influencing TE differentiation in the Zinnia elegans in vitro system.…”
Section: Tracheary Element Differentiation Using Zinnia Elegans Mesopmentioning
confidence: 96%